Vernacular Architectural Preservation of Material and Spiritual Interconnected Cultural Heritage - ALMIRA KHAFIZOVA (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
Vernacular architecture presents sustainable minimum-impact structures harmonized with their context and inhabitants. Heritage preserved tangible and intangible in material forms, encrypted spiritual believes of humanity's life in dwellings’ organization unveiling the details of our ancestors’ life and world cultures’ connectivity. Instigated by modern-world urbanization, sustainability and cultural diversity issues, the study is researching on cultures connectivity, corresponding to the scale and context of the global cityscape and attempting to synthesize vernacular heritage. The objective of this research is to study indigenous human congruent architectural examples and their relationship with intangible aspects of habitat. This paper will be adopting a qualitative method, by which it aims to study and observe various examples so as to analyze interconnections of Siberian Chums and Native-American Tipi, their design driving forces, settlement of the 2nd century BC- Arkaim and Japanese traditional architecture.